Construction of a novel p-n heterojunction CdS QDs/LaMnO3 composite for photodegradation of oxytetracycline. (15th June 2022) - Zhang, Huifang; Wang, Ying; Zhai, Chunyang
Abstract: Semiconductor-driven photocatalysis degradation is deemed as a prospective technology to treat antibiotic contaminants in the aquatic environment. In this work, a novel p-n heterojunction CdS QDs/LaMnO3 composite is proposed and successfully fabricated. The photocatalytic activity of CdS QDs/LaMnO3 composite is evaluated by the application of photocatalytic degradation of OTC (oxytetracycline). The results show that the complex with 5% CdS QDs possesses the superior photocatalytic efficiency of 70%, exceeding that of pristine LaMnO3 and CdS QDs by 43% and 27%, respectively. The improvement of photocatalytic activity can be ascribed to the effective separation of electron-hole pairs between CdS QDs and LaMnO3, and the strong redox ability of free radicals. In addition, through the analysis of active species and the judgment and reasoning process of energy band structure, a most likely p-n heterojunction is proposed. Therefore, CdS QDs/LaMnO3 nanocomposite is expected to be a candidate for this upgraded photocatalytic activity. Graphical abstract: Image 1